Natural Compounds A Weapon to Ameliorate Breast Cancer Cells: A Review - Singh Thakur, Ruchi; Ahirwar, Bharti (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Breast cancer is the heterogeneous disease and leading cause of death in women, worldwide. It is generally caused by the perturbation of various signaling pathways responsible for cell apoptosis. Due to genetic variability, different signaling pathways are disrupted in different breast cancer patients; so, to overcome this multifaceted condition, the personalized treatment is preferred. Since, various potential targets exist in breast cancer cells; it raised the need of new prospective of lead compounds. A large number of evidences show that, due to the presence of various secondary metabolites in plants, natural compounds are frequently examined for search of new bioactive molecules. This review includes the pathological aspects of breast cancer and the effect of natural compounds on breast cancer cells along with their possible mechanism of action. (Databases searched were PubMed, Science Direct, Web of Knowledge, Scopus, and Google Scholar).
Keywords: Caspase